Receptor function of mouse sperm surface galactosyltransferase during fertilization (The Rockefeller University Press, 1985)
Past studies from this laboratory have suggested that mouse sperm binding to the egg zona pellucida is mediated by a sperm galactosyltransferase (GalTase), which recognizes and binds to terminal N-acetylglucosamine (GlcNAc) residues in the zona pellucida (Shur, B. D., and N. G. Hall, 1982, J. Cell Biol. 95:567-573; 95:574-579). We now present evidence that directly supports this mechanism for gamete binding. GalTase was purified to homogeneity by sequential affinity- chromatography on GlcNAc-agarose and alpha-lactalbumin-agarose columns. The purified enzyme produced a dose-dependent inhibition of sperm binding to the zona pellucida, relative to controls. To inhibit sperm/zona binding, GalTase had to retain its native conformation, since neither heat-inactivated nor Mn++-deficient GalTase inhibited sperm binding. GalTase inhibition of sperm/zona binding was not due to steric blocking of an adjacent sperm receptor on the zona, since GalTase could be released from the zona pellucida by forced galactosylation with UDPGal, and the resulting galactosylated zona was still incapable of binding sperm. In control experiments, when UDPGal was replaced with the inappropriate sugar nucleotide, UDPglucose, sperm binding to the zona pellucida remained normal after the adsorbed GalTase was washed away. The addition of UDPGal produced a dose- dependent inhibition of sperm/zona binding, and also dissociated preformed sperm/zona adhesions by catalyzing the release of the sperm GalTase from its GlcNAc substrate in the zona pellucida. Under identical conditions, UDP-glucose had no effect on sperm binding to the zona pellucida. The ability of UDPGal to dissociate sperm/zona adhesions was both time- and temperature-dependent. UDPGal produced nearly total inhibition of sperm/zona binding when the zonae pellucidae were first galactosylated to reduce the number of GalTase binding sites. Finally, monospecific anti-GalTase IgG and its Fab fragments produced a dose-dependent inhibition of sperm/zona binding and concomitantly blocked sperm GalTase catalytic activity. Preimmune IgG or anti-mouse brain IgG, which also binds to the sperm surface, had no effect. The sperm GalTase was localized by indirect immunofluorescence to a discrete plasma membrane domain on the dorsal surface of the anterior head overlying the intact acrosome. These results, along with earlier studies, show clearly that sperm GalTase serves as a principal gamete receptor during fertilization.